Ordering the mess: (re-)defining public schooling as a remedy. (2nd November 2021) - Winandy, Jil; Hemetsberger, Bernhard
ABSTRACT: From the vantage point of present educational policy, it appears fairly straightforward to seek the solution to felt social and societal crises in education. Hence, on the basis of this statement, education can be considered as the most suitable tool to repair a perceived damage or the most effective medicine to cure a diagnosed sickness. Through the lens of "crisis narrations" and their alleged call for more (or a different) structure, the paper seeks to trace the perception of education as a remedy back to the origins of Western (more precisely Austrian and US) mass public schooling. Hence, two case studies, namely the Silesian reformer Johann Ignaz Felbiger and the leader of the later US common school movement, Horace Mann, are used to undermine the thesis of a common pattern of education as a way to cure the alleged weaknesses and consequently to order the (perceived) mess. It is argued that in both, the eighteenth-century Habsburg Empire and the nineteenth-century US, constitutional mindsets, described as "deeply engrained ways of understanding the relation between the public and its institutions", (re-)defined public schooling as a remedy aiming to provide a better future for all the members of the society, independent of their social class.